Positive QRS complex in limb lead 2 with negative QRS in lead 3 on surface electrocardiogram: A novel predictor for anterior location of right‐sided accessory pathways (10−1 o'clock on tricuspid annulus). (28th February 2022) - Bera, Debabrata; Mukherjee, Sanjeev S.; Majumder, Suchit; Sikdar, Sunandan; Dasgupta, Koushik; Kar, Ayan; Kathuria, Sanjeev; Sarkar, Rakesh
Abstract: Background: Localization of atrioventricular accessory pathways (AP) from Electrocardiogram (ECG) is crucial for successful ablation. We analyzed the value of limb lead 2 versus 3 QRS vector discordance on surface ECG among right‐sided pathways. Methods: Data from consecutive patients undergoing successful ablation of manifest AP were analyzed. They were categorized into two groups—Gr I: Endocardial ablation from anterior and anterolateral tricuspid annulus (TA, 10−1 o'clock, right anterolateral [RAL]); Gr II: Ablation outside this region (1−10 o'clock of TA). Inferior lead discordance (ILD) was defined as positive QRS complex (monophasic R, Rs) in lead 2 with negative/equiphasic QRS vector in lead 3 (rS, S, RS). Maximally pre‐excited ECGs during electrophysiology study were compared for presence of ILD. Result: Among total 22 cases (Age 36 ± 18 years, 12 males), ILD was noted in 4/4 cases of Gr I. It was absent among 17/18 cases of right‐sided AP in Gr II. The only case in Gr II having ILD was ablated near 8 o'clock (posterolateral). In contrast to the other four cases, aVF was negative, along with lead 3. A close differential was mid‐septal AP (MSAP). However, the MSAP had absence of r in V1 and lead 2 having rS/RS complex in contrast to strongly positive QRS in RAL pathways. The sensitivity and specificity of ILD for RAL are 100% and 95%, respectively. The positive, negative predictive value, and accuracy are 80%, 100%, and 95%, respectively. Conclusion: Positive QRS complex in lead 2 with negative QRS in lead 3 in maximally pre‐excited ECG is often predictive of anterior and anterolateral location among right‐sided pathways.